1994
DOI: 10.1111/j.1440-1754.1994.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

integrated health and education input in the development of educational resources about asthma for schools

Abstract: The development of educational packages on health-related topics has become common in school curricula. This paper describes an integrated health and education input in the development of an educational package about asthma for Year 8 high school students. Ownership and educational relevance of the package (ensuring its appropriateness for inclusion within the Personal Development/Health/Physical Education curriculum) was achieved by collaboration between teachers with an understanding of the principles of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Although video instruction has been incorporated into various asthma education projects (18), there is only one report of video use with school teacher instruction (15). Although other studies have shown a similar increase in asthma knowledge by school teacher participants (7,8,15,17,20), this is the only study to test a video training component of actual patient footage. Although other studies have shown a similar increase in asthma knowledge by school teacher participants (7,8,15,17,20), this is the only study to test a video training component of actual patient footage.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although video instruction has been incorporated into various asthma education projects (18), there is only one report of video use with school teacher instruction (15). Although other studies have shown a similar increase in asthma knowledge by school teacher participants (7,8,15,17,20), this is the only study to test a video training component of actual patient footage. Although other studies have shown a similar increase in asthma knowledge by school teacher participants (7,8,15,17,20), this is the only study to test a video training component of actual patient footage.…”
Section: Discussionmentioning
confidence: 91%
“…The use of video to instruct nonmedical personnel to visually recognize signs of respiratory distress, however, is uncommon. Although video instruction has been incorporated into various asthma education projects (18), there is only one report of video use with school teacher instruction (15). Although video instruction has been incorporated into various asthma education projects (18), there is only one report of video use with school teacher instruction (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the need for, and acceptance of asthma education by the medical profession has resulted in the ongoing development of a diverse range of programmes. Programmes currently available vary in content and mode of presentation and are suitable for use in a wide range of medical and non-medical settings including hospitals, clinics and general medical practices, community agencies, schools and specialized camps, and family homes (Baxmann & Klimo 1989;Deaves 1993;Punnett 1993;Capan et al 1994;Collins 1994;Henry et al 1994;Alaniz 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, education of society, especially of teachers and school-age children, is as important as education of the patient and the patient’s parents [16]. However, it was shown that education of school teachers did not positively affect adolescents with asthma [17]. Surveys suggest that peers may have a greater influence on a young person’s health behavior than parents or health staff do [9,18,19,20] as adolescents prefer to get information or receive a message about themselves from the peers they trust [21].…”
Section: Introductionmentioning
confidence: 99%